If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 6y = 16 Solving 13x + 6y = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 13x + 6y + -6y = 16 + -6y Combine like terms: 6y + -6y = 0 13x + 0 = 16 + -6y 13x = 16 + -6y Divide each side by '13'. x = 1.230769231 + -0.4615384615y Simplifying x = 1.230769231 + -0.4615384615y
| 2(-7+6x)=-98 | | 7+2h=11 | | 8x+4+7x-4=180 | | 222-(x)2=360 | | 9(p+1)=99 | | 11/15=x/3 | | 9c-6c+2c-1=14 | | 21.00+1.50x=10.00+2.75x | | 3(3)-8=4-3 | | -3(2x-7)=-33 | | 16y^2/4y^-6 | | 21.00+1.50=10.00+2.75 | | 0=2x-8y+10 | | 7x+4(-x+2)=-1 | | 16x+12y=-18 | | 4p-5-5p=-3 | | -12+10x+2x=-132 | | 18x+14=19x+6 | | 1.5x+x=150000 | | 6(-3+2x)=6 | | 17x-14x-2x+3x-3x=13 | | 5(10-4x)=-150 | | -4(3x-2)=48 | | z^2-10z+18=0 | | 10.75t=1006.25 | | -7(4x-5)=63 | | 7(5x-1)=-147 | | 0.7x=0.49 | | F(x)=a*sen(pi-2x)+1 | | 30x+2=29x+1 | | 4p+2p=-12 | | 10y-5=23 |